Evaluation of strontium-site-deficient Sr2Fe1.4Co0.1Mo0.5O6−δ-based perovskite oxides as intermediate temperature solid oxide fuel cell cathodes. (15th June 2016) - Zhen, Shuying; Sun, Wang; Tang, Guangze; Rooney, David; Sun, Kening; Ma, Xinxin
Abstract: In this paper strontium-site-deficient Sr2 Fe1.4 Co0.1 Mo0.5 O6−δ -based perovskite oxides (Sx FCM) were prepared and evaluated as the cathode materials for intermediate temperature solid oxide fuel cells (IT-SOFCs). All samples exhibited a cubic phase structure and the lattice shrinked with increasing the Sr-deficiency as shown in XRD patterns. XPS results determined that the transition elements (Co/Fe/Mo) in Sx FCM oxides were in a mixed valence state, demonstrating the small polaron hopping conductivity mechanism existed. Among the samples, S1.950 FCM presented the lowest coefficient of thermal expansion of 15.62 × 10 −6  K −1, the highest conductivity value of 28 S cm −1 at 500 °C, and the lowest interfacial polarization resistance of 0.093 Ω cm 2 at 800 °C, respectively. Furthermore, an anode-supported single cell with a S1.950 FCM cathode was prepared, demonstrating a maximum power density of 1.16 W cm −2 at 800 °C by using wet H2 (3% H2 O) as the fuel and ambient air as the oxidant. These results indicate that the introduction of Sr-deficiency can dramatically improve the electrochemical performance of Sr2 Fe1.4 Co0.1 Mo0.5 O6−δ, showing great promise as a novel cathode candidate material for IT-SOFCs. Highlights: Strontium-site-deficient Sr2 Fe1.4 Co0.1 Mo0.5 O6−δ oxides are prepared and evaluated. The TEC and electrical conductivity values firstly decrease and then increase. Sr1.950 Fe1.4 Co0.1 Mo0.5 O6−δ shows the lowest ASR value of 0.093 Ω cm 2 at 800 °C. A maximum power density of 1.16 W cm −2 is achieved by single cell with S1.950 FCM cathode at 800 °C.